Possible Therapeutic Application of Targeting Type II Natural Killer T Cell-Mediated Suppression of Tumor Immunity - Kato, Shingo; Berzofsky, Jay A.; Terabe, Masaki (Frontiers in Immunology, 2018)
Natural killer T (NKT) cells are a unique T cell subset that exhibits characteristics from both the innate immune cells and T cells. There are at least two subsets of NKT cells, type I and type II. These two subsets of NKT cells have opposite functions in antitumor immunity. Type I NKT cells usually enhance and type II NKT cells suppress antitumor immunity. In addition, these two subsets of NKT cells cross-regulate each other. In this review, we mainly focus on immunosuppressive NKT cells, type II NKT cells. After summarizing their definition, experimental tools to study them, and subsets of them, we will discuss possible therapeutic applications of type II NKT cell pathway targeted therapies.